The Impact of The COVID-19 Pandemic on The Implementasion of Online Learning in MI Islamiyah Lamongan - Fashi Hatul Lisaniyah; Ummidlatuss Salamah (Madrosatuna: Journal of Islamic Elementary School, 2021)
The COVID-19 pandemic has an impact not only on health, but also on education. The world of education has undergone major changes. The reason is, to prevent the spread of COVID-19 from becoming more widespread, the government requires teachers and students not to do face-to-face learning at school, and replace it with learning at home or better known as online learning. However, in reality online learning is not as effective as direct learning, because students cannot interact optimally in the learning process. In addition, online learning has also caused many polemics, remembering that online learning is new learning for students, that's why researchers are interested in conducting research related to the impact of the COVID-19 pandemic on online learning with the title Impact of the COVID-19 pandemic on the online learning process at MI Islamiyah. The purpose of this study is to obtain information about the impact of COVID-19 on the implementation of online learning in elementary schools. Is online learning in primary schools can be done well and effectively. This research uses an exploratory study research method, with a qualitative case study approach. The results of this study, the impact on students, namely, students feel bored and bored doing online learning. And students are required to adapt to distant learning or online. Furthermore, the impact for teachers, not all teachers are proficient in using social media to support online learning. Teachers are burdened by the additional cost of internet quota and inadequate facilities owned by teachers. The last impact is the impact felt by parents, in addition to paying tuition fees, parents are burdened with the cost of purchasing an internet quota package. and working parents must share their time by accompanying their children to online learning.